Eksplorasi Potensi Kemaritiman Kabupaten Pangandaran: Perspektif Sosio-Budaya dan Ekonomi dalam Rentang Waktu 2012-2024 - Setianingsih, Sarah; Yulifar, Leli (Jurnal Artefak, 2025)
Pangandaran Regency is a New Autonomous Region (DOB) that was formed in 2012. The formation of this DOB was motivated by the desire of the community to advance and develop in various aspects. This region is considered capable of becoming a DOB because of its great potential, especially in the economic sector. The research aims to look at the beginning of Pangandaran becoming a DOB, its socio-cultural economic conditions and the exploration of maritime potential in it. By using the historical method, including heuristics, criticism, interpretation and historiography, the research tries to describe how maritime potential in the socio-cultural economic perspective. Through this perspective, it is concluded that this Regency has great potential in the maritime sector, especially in the socio-cultural economic aspect. However, its management has not been maximised, as seen from its economic income which is not large enough and still tends to fluctuate. As a DOB, this Regency has not been able to optimally utilise its potential. Therefore, it needs attention, utilisation, and good management. The research recommends the need to raise awareness regarding the utilisation of maritime potential and must be developed and managed appropriately, for the welfare of the community.